Leroy Jenkins, a violinist in the bass clef (Ex Chordis, 2023)
Undisputed protagonist of the avant-garde in the A.A.C.M. sphere (Association for the Advancement of Creative Musicians), the African-American violinist Leroy Jenkins (Chicago 1937 ⎻ New York 2007) is still a little-studied figure. In his work, he linked sacred music, blues, jazz, radical improvisation and European music. Musical materials that connect and collide, almost dramatizing the events of a life full of contradictions. The focus of this essay is an in-depth analytical study (where possible comparing different versions) of some tunes by Leroy Jenkins from which his very special focus on the bass line is evident; the pieces here analysed date from 1978 to 1992, a period in which part of his musical research concentrated on the potential of electric instruments. The tunes here analyzed are: Looking for the Blues; Through the Ages, Jehovah; Bird Eddie and Monk. However, we only have phonographical traces as text. So, for a musical analysis, we used two tools: transcription in traditional notation and formal diagrams. Therefore, the musical analysis shows: (i) how his thinking as a composer/improviser is not limited to his instrument; (ii) the pieces examined are all based on riffs or bass lines; (iii) moreover, their form is organised in ever-changing ways. Jenkins’ vision as a composer is evident, and the sound of his violin safely directs the flow of sound, yet the music remains extremely free, and this is perhaps the paradoxical essence of free jazz: the coexistence of anarchy and hierarchy.
Keywords: Leroy Jenkins; Free Jazz; Music Analysis; Violin